The Potential and Limitations of the Project Method in Encoraging Student Creativity in Teaching Social, Environmental and Scientific Education - Snežana L. Prtljaga; Aleksandar M. Stojanović; Sanja R. Blagdani (University of Belgrade, Teacher Education Faculty, 2018)
Drawing upon the current trends in modern society, the paper presents a possible way in which education (based on the relationship didactics) can have a positive influence on the development of student multiperspectivism, creativity, and innovations. The paper looks at the potential and limitations of the project method as a factor in encouraging student creativity. The aim of the research was to determine to what extent the use of direct method in teaching Social, Environmental and Scientific Education can encourage creative reactions of students. An experiment with parallel groups was conducted in the research.. The results obtained by means of a modified Guilford and Torrance's creativity test battery have shown that using the direct method in the classroom has a positive effect on associative fluency, fluency and originality of ideas, elaboration, flexible thinking and sensitivity to problems. Despite the fact that certain limitations do exist and that the ultimate effectiveness of the direct method application in our schools cannot be determined with absolute certainty, the obtained results clearly indicate that the direct method has potential to strengthen student creativity.